Efficacy of the ChAdOx1 nCoV-19 Covid-19 vaccine against the B.1.351 variant - Madhi, SA; Baillie, V; Cutland, CL; Voysey, M; Koen, AL; Fairlie, L; Padayachee, SD; Dheda, K; Barnabas, SL; Bhorat, QE; Briner, C; Kwatra, G; et al. (Massachusetts Medical Society, 2021)
Background Assessment of the safety and efficacy of vaccines against the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in different populations is essential, as is investigation of the efficacy of the vaccines against emerging SARS-CoV-2 variants of concern, including the B.1.351 (501Y.V2) variant first identified in South Africa.